Pelatihan Logika Dasar Pemrograman menggunakan Code.org pada SMA Negeri 1 Bergas - Winarsih, Nurul Anisa Sri; Pramunendar, Ricardus Anggi; Saputra, Filmada Ocky; Rohman, Muhammad Syaifur; Ratmana, Danny Oka; Hamid, Maulana As’an; Kartika, Gita (LPPM UNIVERSITAS DIAN NUSWANTORO, 2025)
Program